The important conversation around revising the DPR rules of procedure: Understanding its impact on the principle of separation powers in Indonesia - Mochammad Rafsyanjani (Universitas Negeri Yogyakarta, 2025)
The revision of the House of Representatives Rules of Procedure No. 1 of 2020 has sparked controversy because it grants the House of Representatives new authority to recommend the dismissal of state institution leaders who have undergone a fit and proper test. This is considered to exceed the House of Representatives' oversight function and potentially undermines the principle of separation of powers and the independence of state institutions as stipulated in the 1945 Constitution. This study employs a qualitative descriptive method to examine the impact of the revision from a legal-political perspective. The findings indicate that the DPR's rules of procedure should be internal and cannot serve as a legal basis for removing the leadership of independent institutions whose provisions are already regulated by separate laws. This revision is feared to create political conflicts of interest and undermine the system of checks and balances in state governance. Therefore, the DPR should not exceed its authority in performing its oversight function. This study also acknowledges the limitations of the data and recommends further research with a broader scope.